Legal status of the president of the national authority, the council of ministers and legislative council in Palestine - Hamad, Ahmed Mohammed Adnan (2022)
The Basic Law of 2003 stipulates that the governing system in Palestine is a parliamentary democratic system based on political and party pluralism, in which the President is elected directly by the people. Article 2 of the Basic Law 2003 provides that the people of Palestine are the source of power, which shall be exercised by the authorities based upon the principle of separation of powers. The Council of Ministers is accountable to the President and the Legislative Council. However, the Palestinian legal system is currently facing a legal gap. The ambiguity and discrepancy of legal provisions regulating the relationship between the authorities have led to an overlapping of powers and functions between the President, the Council of Ministers, and the Legislative Council. Moreover, political division between the Gaza Strip and the West Bank also contributes to the overlapping of powers and functions between the authorities. Overlapping of powers covers many fields such as legislative, security, financial and appointment to senior positions. This research aims to identify the powers and functions of the President, the Council of Ministers, and the Legislative Council, the overlapping of powers and functions between these authorities and the impact of political division between the Gaza Strip and the West Bank on the Palestinian legal system. To achieve these objectives, socio-legal research using interviews as a tool for qualitative research was engaged. The results proved that there is an overlapping in the powers and functions between the President, the Council of Ministers and the Legislative Council in many fields. In addition, the political division also brought a negative impact on their relationship. The results suggest amending the provisions of the Basic Law 2003 and related laws by removing ambiguity and discrepancy to prevent this overlapping of powers and functions between the President, the Council of Ministers, and the Legislative Council. Furthermore, presidential and legislative elections should be conducted in Palestine to put an end to political division and activating the role of the Supreme Constitutional Court will help to provide a solution to the problems, therefore, achieving the objectives of this study.